REVAMPING AN INTENSIVE ENGLISH LANGUAGE PROGRAM: CHALLENGES AND INNOVATIONS - Saleh Salim Al-Busaidi (Indonesian JELT, 2006)
This article describes an attempt to reform a curriculum of an English intensive language program in the Sultanate of Oman. The reform consisted of several stages, starting from the identification of needs until choosing teaching materials. Based on the data obtained from the various sources of the study (i.e. survey, observations, interviews, and workshops), a number of changes were introduced to the curriculum. This project revealed important issues to be addressed in order to make the program design and evaluation more effective in upgrading students’ English language proficiency and academic competence so that they are better prepared for college study. Keywords: English intensive language program, English language proficiency, academic competence